The impact of economic freedom on economic growth? New European dynamic panel evidence - Ivana Brkić; Nikola Gradojević; Svetlana Ignjatijević (Journal of Risk and Financial Management, 2020)
This paper analyzes the impact of economic freedom along with traditional economic factors on economic growth for a panel of European countries. The growth of the gross domestic product was observed over a twenty-year time period on a sample of 43 developing and developed countries. Based on a robust dynamic panel setting, we conclude that increases in economic freedom as expressed by the Index of Economic Freedom/Heritage Foundation (but not its levels) are related to economic growth. The EU membership status either had no effect or it curbed the effect of the economic freedom on growth. We also find that the subprime economic crisis of 2008-2009 exerted a negative impact on the growth of European economies.
Keywords: 330; economic freedom; economic growth; Europe; panel analysis; subprime crisis; system GMM